Sustainable Vertical Housing Based on Social and Cultural Activities - Ulya Nur Rahmah Ellyanando, Adinda; Tisnawati, Endah; Suparno, Suparno (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
The development of vertical housing is currently a response to the problem of population increase. People with low incomes (MBR) who have a range of restrictions, from knowledge gaps to financial difficulties, are typically the ones who live in vertical housing in developing nations like Indonesia. Due to misunderstandings about residents' social and cultural behavior and activities addressing the culture of living in multi-story residences, there are many issues with vertical housing these days, particularly those pertaining to disorganization and improper use of space. The careless use of hallways, which leaves them cluttered with trash, clotheslines, and the possessions of residents, is one issue that frequently arises. This study will outline the issues with vertical housing in Bandung City and provide examples of well-designed housing in the past. The study aims to offer best practices for bridging the gap between the existing conditions and the vertical housing usage pattern. Furthermore, it is anticipated that the findings will lead to both intelligent spatial utilization and sustainable architectural design solutions.